Spheroid assembly of mesenchymal stem cells enhances secretome-mediated corneal reinnervation and epithelial repair in a mouse model of experimental dry eye - Shao-Wen Liu; Meng-Yu Tsai; Yang-Chun Shen; Yi-Jen Hsueh; Han Chiu; Li-Wen Hsu; Hung-Chi Chen; Chieh-Cheng Huang (Journal of Tissue Engineering)
Dry eye disease is a complex ocular surface disorder with multifactorial pathophysiology, including corneal epithelial damage, chronic inflammation, and corneal nerve dysfunction. Among these, impaired corneal innervation plays a particularly critical role, as it disrupts neurotrophic support and tear reflexes, perpetuating disease progression, and delaying healing. However, conventional treatments often provide only temporary symptom relief without addressing underlying tissue damage or promoting nerve regeneration. This shortcoming highlights the need for therapies that not only suppress inflammation but also restore corneal innervation. In this study, we evaluated the therapeutic potential of mesenchymal stem cell (MSC) spheroid-derived secretome—a cell-free solution rich in regenerative and anti-inflammatory factors—in a preclinical mouse model of dry eye disease. Compared with untreated controls, eyes treated with the MSC spheroid secretome presented faster corneal epithelial regeneration, improved corneal nerve reinnervation, and reduced inflammatory cell infiltration. These findings demonstrate that the MSC spheroid-derived secretome can simultaneously target multiple pathological features of dry eye to promote recovery of ocular surface integrity, underscoring its potential as a clinically relevant, cell-free regenerative therapy for dry eye and other ocular surface disorders.